Incidence and risk factors for anastomotic bile leakage in hepatic resection with bilioenteric reconstruction – A international multicenter study. Issue 1 (January 2023) - Braunwarth, Eva; Ratti, Francesca; Aldrighetti, Luca; Al-Saffar, Hasan A.; D`Souza, Melroy A.; Sturesson, Christian; Linke, Richard; Schnitzbauer, Andreas; Bodingbauer, Martin; Kaczirek, Klaus; Vagg, Daniel; Toogood, Giles; et al.
Abstract: Background: Anastomotic leak (AL) after bilioenteric reconstruction (BR) is a feared complication after bile duct resection, especially in combination with liver resection. Literature on surgical outcome is sparse. This study aimed to determine the incidence and risk factors for AL after combined liver and bile duct resection with a focus on operative or endoscopic reinterventions. Methods: Data from consecutive patients who underwent liver resection and BR between 2004 and 2018 in 11 academic institutions in Europe were collected from prospectively maintained databases. Results: Within 921 patients, AL rate was 5.4% with a 30d mortality of 9.6%. Pringle maneuver (p<0.001), postoperative external biliary (p=0.007) and abdominal drainage (p<0.001) were risk factors for clinically relevant AL. Preoperative biliary drainage (p<0.001) was not associated with a higher rate of AL. AL was more frequent in stented patients (76.5%) compared to PTCD (17.6%) or PTCD+stent (5.9%, p=0.017). AL correlated with increased incidence of postoperative liver failure (p=0.036), cholangitis, hemorrhage and sepsis (all p<0.001). Conclusion: This multicenter data provides the largest series to date of LR with BR and could help in the management of these patients which are often challenging and hampering the patients' postoperative course negatively.